Mad, sad or bad. Moral luck and Michael Stone - Noguera, Anita R. (Nursing philosophy, 2000)
This paper discusses the philosophical doctrine of moral luck, as described by Bernard Williams in his book of the same name. It first describes Williams' account and then uses the case of Michael Stone, a convicted murderer with a long history of mental disorder, and mental health practitioners’ interventions in his case, to test and debate Williams’ views. It examines four major areas of these, including the classical notion of moral luck, retroactive judgement, agent regret and justifiable and unjustifiable decision-making. It concludes that, in view of what has been said, whilst Williams’ views are applicable and appropriate to many areas of the Stone case, ‘traditional’ moral views on rights, obligations and principles cannot be entirely laid aside in evaluating this.